(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Albizia lebbeck (Linn.) Benth. is a deciduous tree which is planted as ornamental and avenue tree almost all over Bangladesh. Leaves of the plant are used in ethnomedicine for the treatment of convulsion and CNS related disorder. This study was aimed to evaluate the neuropharmacological effects of the methanol extract of A. lebbeck leaves in Swiss albino mice. The locomotor effect of crude methanol extract of the plant was investigated by open field and hole cross tests while the anxiolytic activity was determined using elevated plus-maze (EPM) and light/dark box (LDB) tests. Furthermore, the sedative activity of the plant extract was assessed by sodium thiopental-induced sleeping time test. The results demonstrated that the methanol extract significantly (p < 0.001) reduced locomotion of the animals in both hole cross and open field tests in dose-dependent manner at 200-400 mg/kg b.w. In both EPM and LDB tests, the plant extract produced significant anxiolytic effect (p < 0.05) at the doses of 100-400 mg/kg b.w. In addition, it showed significant (p < 0.001) dose-dependent decrease in the onset of sleep and an increase in duration of sleep in sodium thiopental-induced sleeping time test. Preliminary phytochemical analyses of the plant extract revealed the presence of alkaloid, flavonoid, glycoside, saponin, tannin and resin. In acute toxicity test, the leaf extract did not exhibit any adverse effect in mice during 7 days treatment. The results of the present studies suggest that the crude methanol extract of A. lebbeck leaves possesses significant CNS depressant, anxiolytic and sedative properties and rationalize the traditional uses of the plant. Bangladesh Pharmaceutical Journal 21(2): 80-86, 2018